Alogliptin improves survival and health of mice on a high‐fat diet. Issue 2 (15th January 2019) - Zhu, Biao; Li, Yixiang; Xiang, Lingwei; Zhang, Jiajia; Wang, Li; Guo, Bei; Liang, Minglu; Chen, Long; Xiang, Lin; Dong, Jing; Liu, Min; Mei, Wen; et al.
Abstract: Alogliptin is a commonly prescribed drug treating patients with type 2 diabetes. Here, we show that long‐term intervention with alogliptin (0.03% w/w in diet) improves survival and health of mice on a high‐fat diet. Alogliptin intervention takes beneficial effects associated with longevity, including increased insulin sensitivity, attenuated functionality decline, decreased organ pathology, preserved mitochondrial function, and reduced oxidative stress. Autophagy activation is proposed as an underlying mechanism of these beneficial effects. We conclude that alogliptin intervention could be considered as a potential strategy for extending lifespan and healthspan in obesity and overweight.